TLR9 acts as a sensor for tumor-released DNA to modulate anti-tumor immunity after chemotherapy. Issue 1 (16th October 2019) - Kang, Tae Heung; Mao, Chih-Ping; Kim, Young Seob; Kim, Tae Woo; Yang, Andrew; Lam, Brandon; Tseng, Ssu-Hsueh; Farmer, Emily; Park, Yeong-Min; Hung, Chien-Fu
Abstract : The tumor microenvironment exists in a state of dynamic equilibrium, in which a balance of agonist and antagonist signals govern the anti-tumor immune responses. Previous studies have shown that chemotherapy could shift this balance in favor of agonistic signals for the anti-tumor immune responses mounted by CD8+ cytotoxic T lymphocytes (CTL), providing sufficiently high antigen density within the tumor. We undertook the current study to characterize the anti-tumor immune response following chemotherapy and its underlying mechanisms. We show that this 'adjuvant effect' of chemotherapy is, at least partially, mediated by the release of tumor DNA and acts through the Toll-like receptor 9 (TLR9) pathway. We found that tumor-released DNA causes accumulation, antigen uptake, and maturation of dendritic cells (DCs) in the tumor in a TLR9-dependent manner. These DCs subsequently migrate into the draining lymph nodes and prime tumor-specific CTLs. Our study provides novel insights to the molecular and cellular mechanisms by which chemotherapy converts the tumor microenvironment into a site permissive for the activation of a potent tumor-specific adaptive immune response.